The mental health of asylum seekers in Australia and the role of psychiatrists - Silove, Derrick (BJPsych Int, 2018)
There are more displaced people around the world than ever before, and over half are children. Australia and other wealthy nations have implemented increasingly harsh policies, justified as ‘humane deterrence’, and aimed at preventing asylum seekers (persons without preestablished resettlement visas) from entering their borders and gaining protection. Australian psychiatrists and other health professionals have documented the impact of these harsh policies since their inception. Their experience in identifying and challenging the effects of these policies on the mental health of asylum seekers may prove instructive to others facing similar issues. In outlining the Australian experience, we draw selectively on personal experience, research, witness account issues, reports by human rights organisations, clinical observations and commentaries. Australia’s harsh response to asylum seekers, including indefinite mandatory detention and denial of permanent protection for those found to be refugees, starkly demonstrates the ineluctable intersection of mental health, human rights, ethics and social policy, a complexity that the profession is uniquely positioned to understand and hence reflect back to government and the wider society.